Caracterização das alterações transcricionais e morfológica da mitocôndria da prole de fêmeas obesas com deficiência da mitofusina 2 no oócito - Ferreira, Renan Omete (Universidade Federal de São Carlos, 2024)
Heart disease is one of the main causes of death worldwide and research has shown an intrinsic relationship between cardiac effects in offspring and maternal obesity. In addition, there is increasing evidence of the possible involvement of mitochondria in oocytes as factors that contribute to the maternal effect. Thus, these alterations end up being passed on to the offspring and are associated with metabolic and cardiac disorders. Therefore, MFN2, an important modulator of metabolism that is located in the mitochondria and the ER, appears to play a fundamental role in transmitting metabolic conditions and changes to the offspring. With this information in mind, the current study sought to determine the transcriptional changes and mitochondrial morphology in the cardiac tissue of mice born to obese mothers with oocyte-specific MFN2 knockouts. For this purpose, cardiac tissues were collected from the offspring of obese females with oocyte-specific knockout of MFN2 and wild males. After collection, the RNA content of these tissues was extracted and purified for the production of RNA-Seq libraries, assessing the quality and quantity of the transcript, subsequently converting it into cDNA by attaching adapters to the ends of the molecule, followed by sequencing and the generation of differential expression data. In this way, the levels of transcription in cardiac tissue were assessed, as well as the main differentially regulated pathways, using the DAVID platform and the RStudio integrated development environment for differential expression analysis. In addition, we sought to determine parameters of mitochondrial morphology in the tissue of the offspring of these obese females with oocyte-specific MFN2 knockouts by obtaining transmission electron microscopy images and analyzing them using ImageJ software. Thus, the results indicated a profound change in the transcription in cardiac tissue of these animals, with impacts on the oxidative phosphorylation pathway and related to diabetic cardiomyopathy, despite insignificant changes in the quantitative analysis of mitochondrial morphology. Therefore, the MFN2 knockout is related to the transmission of effects at the transcriptional level in the cardiac tissue of the offspring.
Characterisation of transcriptional and morphological mitochondrial alterations in the offspring born to obese females with oocyte deficiency of mitofusin 2
Keywords: MFN2; Mitocôndria; Mitochondria; Coração; Heart; CIENCIAS BIOLOGICAS::GENETICA